KADAR HEMOGLOBIN (Hb) PENDERITA TB PARU DALAM MASA TERAPI OAT (OBAT ANTI TUBERKULOSIS) DI PUSKESMAS HAJI ABDUL HALIM HASAN BINJAI - Fauziah, Ida; Siahaan, Grace Evalina (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2014)
ABSTRACTThe study was conducted to observe the haemoglobin level in pulmonary tuberculosis (TB) patient in therapeutic period who received anti tuberculose drugs. Hemoglobin level of Thirty Pulmonary TB patients was examined each month, before receiving any therapy and after the medications was given. Hemoglobin level measurement was continued until the third month of therapy. The observation held at Haji Abdul Halim Hasan Public Health Center in Binjai showed that the hemoglobin level was significantly decrease with the time in pulmonary TB patient especially at the third month of therapy both in male and female patients.